A nutrition intervention study’s effect to hematology profiles on elderly group in social retirement home - Sudargo, Toto; Suryani, Dyah; Widyaningrum, Rachmawati; Prameswari, Atika Anif; Aulia, Bianda; Sumayyah, Sumayyah; Setyawening, Annisa Luthfia; Putri, Sheila Rosmala (Intelektual Pustaka Media Utama, 2024)
The increase in the elderly brings consequences, including a higher risk of disease. Inappropriate nutritional intake is also known as one of the risk factors related to the elderly's non-communicable diseases, and nutritional intervention is essential to improve the elderly nutritional status and quality of life. It was an interventional study with a before-after one-group approach. The study was conducted for three months (October-December 2021) in three social retirement homes. The intervention given was supplementation with additional protein sources and snacks each day. The biochemistry profiles were taken 2 times: before and after three months of intervention, comprised of HbA1c, lipid, transferrin, creatinine, and blood pressure level. The data will be analyzed for its normality before being processed with paired t-test or Wilcoxon signed rank based on the normality results. The analysis results show that there are significantly lower transferrin levels (p=0.040), an increase in cholesterol level (p=0.000), and low-density lipoprotein (LDL) level increased from 114.05±32.03 to 125.94±31.41 (p=0.000). There is also a remarkable decrease in hemoglobin (p=0.005) and high-density lipoprotein (HDL) levels. Conversely, there are an increase in HbA1C (p=0.007) and triglyceride level (p=0.005). There is no significant difference in creatinine level. We conclude that nutrition interventions have a significant effect on elderly blood profiles. However, to achieve an improvement, the study should consider physical activity and other variables that might be altering the results.